Pengaruh Aromaterapi Minyak Atsiri Mawar terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif di Puskesmas Cisoka Kabupaten Tangerang Banten - Widiarti, Siti Mugiya; Tahun, Omega DR (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT In the active phase of first stage of labor, uterine contractions become more frequent, longer Background: In the active phase of first stage of labor, uterine contractions become more frequent, longer and more intense. The pain that occurs during this phase can affect the birth experience and the mother's comfort. Therefore, reducing pain in this phase is important. The aroma that comes from Rose Essential Oil aromatherapy works to influence a person's emotions with the limbic (via the olfactory system) and the emotional center of the brain. To determine the effect of rose essential oil aromatherapy on the intensity of labor pain in the first stage of the active phase at the Cisoka Community Health Center, Tangerang Banten Regency in 2024. Assessment of the intensity of labor pain using the Visual Analogue Scale (VAS) instrument before and after giving aromatherapy for 10 minutes. for 3 months from April to June 2024. The total respondents in this study were 30 respondents taken by purposive sampling. Data analysis was carried out. Statistical tests in this study were univariate analysis using central tendency and bivariate analysis using the dependent t-test (paired sample t). -test). Independent sample statistical test results t test value Sig. (2-tailed), namely 0.000, where 0.000 < 0.05, it can be concluded that there is a difference between giving and not giving essential oil aromatherapy to mothers in the first stage of labor. So the results of this study can be concluded that there is an influence of rose essential oil aromatherapy on pain intensity. Active phase first stage of labor at Cisoka Community Health Center, Tangerang Banten Regency in 2024. This method can be applied by mothers during labor as an intervention that is safe, comfortable and can help relieve pain. Keywords: Rose Essential Oil Aromatherapy, Intensity of Labor Pain in the First Stage of the Active Phase  ABSTRAK Pada persalinan kala I fase aktif, kontraksi rahim menjadi lebih sering, lebih lama’ dan lebih intens. Rasa nyeri yang timbul saat fase ini dapat mempengaruhi pengalaman persalinan dan kenyamanan ibu. Oleh karena itu, pengurangan nyeri pada fase ini menjadi penting. Aroma yang berasal dari aromaterapi Minyak Atsiri Mawar bekerja mempengaruhi emosi seseorang dengan limbic (lewat sistem olfaktori) dan pusat emosi otak. Untuk Mengetahui Pengaruh Aromaterapi Minyak Atsiri Mawar Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif Di Puskesmas Cisoka Kabupaten Tangerang Banten Tahun 2024. Penilaian  intensitas  nyeri  persalinan  ini  menggunakan  instrumen Visual Analogue Scale (VAS) sebelum  dan  sesudah  pemberian  aromaterapi  selama  10 menit. selama 3 bulan terhitung April sampai Juni 2024. Total reponden dalam penelitian ini adalah 30 responden  yang diambil dengan cara puposif sampling Analisis data dilakukan Uji statistik dalam penelitian ini dengan analisis univariat menggunakan tendensi sentral dan analisis bivariat menggunakan uji dependent t-test (paired sample t-test). Hasil uji statistic independen sampel t tes nilai Sig. (2-tailed) yaitu 0,000 yang mana 0,000 < 0,05 maka dapat di simpulkan ada perbedaan antara diberikan dan tidak diberikan aromaterapi minyak atsiri pada ibu bersalin kala I Sehingga hasil penelitian ini dapat di simpulkan terdapat adanya pengaruh aromaterapi minyak atsiri mawar terhadap intensitas nyeri persalinan kala I fase aktif di Puskesmas Cisoka Kabupaten Tangerang Banten Tahun 2024. Metode ini dapat diterapkan oleh ibu bersalin dalam proses persalinan sebagai intervensi yang aman, nyaman, dan dapat membantu meredakan rasa nyeri. Kata Kunci: Aromaterapi Minyak Atsiri Mawar, Intensitas Nyeri Persalinan Kala I Fase Aktif